2021
DOI: 10.1021/acs.energyfuels.1c00190
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Closed Pores in Longmaxi Shale by Synchrotron Small-Angle X-ray Scattering

Abstract: The characterization of closed and open pore structures is key to evaluating the migration mechanism of gas in shales. In this study, we combined small-angle X-ray scattering (SAXS) with two fluid intrusion methods (low-pressure N2 physisorption and mercury intrusion capillary pressure) to systematically characterize the closed pores of samples from the Longmaxi Formation shale in the Sichuan Basin, China. The total porosity (including connected pores and closed pores) of the shale was measured by SAXS, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Apart from inorganic rocks, the shale matrix actually contains abundant organic matter. ,, The previous studies have shown that the transport behaviors of shale oil and gas in inorganic and organic pores are significantly different. , Compared with the quartz surface, kerogen surface is rougher and has stronger interactions with gas and oil molecules. ,, Therefore, a series of kerogen pore throats with different sizes were calculated for the comparison of gas and oil migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from inorganic rocks, the shale matrix actually contains abundant organic matter. ,, The previous studies have shown that the transport behaviors of shale oil and gas in inorganic and organic pores are significantly different. , Compared with the quartz surface, kerogen surface is rougher and has stronger interactions with gas and oil molecules. ,, Therefore, a series of kerogen pore throats with different sizes were calculated for the comparison of gas and oil migration.…”
Section: Resultsmentioning
confidence: 99%
“…These studies enhanced our understanding on the transport and migration behavior of gas and oil in through nanopores. Apart from through pores, there are also a large number of closed pores and blind pores containing oil. ,, The unconnected closed pores can also be transformed into blind pores with recovery potential after large scale hydraulic fracturing . Blind pores are usually linked to a microfracture through a pore throat.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, physical methods to estimate pore structural parameters of shales include molecular probe adsorption (MPA) such as carbon dioxide (CO 2 ) adsorption and N 2 adsorption and desorption, mercury intrusion porosimetry (MIP), the synchrotron small-angle X-ray scattering method (SAXS), and nuclear magnetic resonance (NMR) . In our study, the micropore parameters of the sample were determined via CO 2 adsorption because of its strong accessibility to ultramicropores and micropores. , It was conducted using an ASAP 2020 adsorption analyzer (Micromeritics).…”
Section: Methodsmentioning
confidence: 99%
“…Ning et al proposed that the difference in the pore size distribution of MIP (reflection of connected pores) and single-phase-fluid saturated NMR T 2 spectrum (reflection of total pores) can indicate the distribution of the nonconnected pores. 68 Similarly, Zhang et al 65 and Wang et al 149 attributed the difference in PSD obtained from MIP (connected pores) and SAXS/SANS (total pores) to the existence of the nonconnected porosity and calculated the proportion of these pores. The above two studies indirectly indicate the structure of nonconnected pores by comparing the differences in the pore structural information that can be measured by different methods.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%